Connecting Medieval and Renaissance Manuscript Collections. Issue 2 (2nd November 2018) - Burrows, Toby
This article examines issues affecting the reuse of data relating to collections of medieval and Renaissance manuscripts in libraries, museums and archives. These manuscripts are increasingly being made available in digital formats, although the extent is perhaps less than expected; a recent report on the situation in Germany estimated that only about 7.5% of the country's 60, 000 manuscripts had been digitized. Discovering these manuscripts is heavily dependent on the quality and consistency of descriptive data about them, but the current situation is very mixed and inconsistent, despite several national programmes (such as Manuscriptorium in the Czech Republic, e-codices in Switzerland, and Biblissima in France) and a major international effort by Europeana . This article reports on recent work in manuscript studies, drawing on two major international projects. The first, funded by the European Union between 2014 and 2016, focused on the manuscript collection assembled in the nineteenth century by Sir Thomas Phillipps. It investigated ways of reconstructing the history of this vast, but now-dispersed collection, by bringing together data from a range of digital and non-digital sources. The second project, Mapping Manuscript Migrations, funded by the Trans-Atlantic Platform under its Digging into Data Challenge from 2017 to 2019, extends the earlier work to a much larger scale, and implements a Linked Open Data framework for combining and managing data related to medieval and Renaissance manuscripts. It enables large-scale analysis and visualization of their history and movements over the centuries.